Control Points Selection Based on Maximum External Reliability for Designing Geodetic Networks - Marcelo Tomio Matsuoka; Vinicius Francisco Rofatto; Ivandro Klein; Maurício Roberto Veronez; Luiz Gonzaga da Silveira; João Batista Silva Neto; Ana Cristina Ramos Alves (Applied Sciences, 2020)
A set of stable and identifiable points—known as control points—are interconnected by direction, distance or height differences measurements form a geodetic network. Geodetic networks are used in various branches of modern science, such as monitoring the man-made structures, analysing the crustal deformation of the Earth, establishing and maintaining a geospatial reference frame, mapping, civil engineering projects and others. One of the most crucial components for ensuring the network quality is Geodetic Network Design. The design of a geodetic network depends on its purpose. In this paper, an automatic procedure for selection of control points is proposed. The goal is to find the optimum control points location so that the maximum influence of an anomaly measurement (outlier) on the coordinates of the network is minimum. Here, the concept of Minimal Detectable Bias defines the size of the outlier and its propagation on the network coordinates is used to describe the external reliability. The proposed procedure was applied to design a levelling network. Two scenarios were investigated: design of a network with one control point (minimally constrained levelling network) and another with two control points (over-constrained levelling network). The centre of the network was the optimum position to set the control point. Results for that network reveal that the centre of the network was the optimum position to set the control point for the minimal constraint case, whereas the over-constraint case were those with less line connections. We highlight that the procedure is a generally applicable method.